Effect of information management on performance of public institutions in Kisii County - Moriasi, Benaditta Kemunto; Muturi, Prof. (Journal of Public Policy and Administration, 2019)
Purpose: The study aimed at investigating the effect of information management on performance of public institutions in Kisii County. Methodology: This study used descriptive survey design. The accessible target population was 200 consisting of top managers and departmental heads in public institutions in Kisii County. This brought the total sample of respondents to 60. The selected respondents were the top level managers and supervisors of public institutions. The respondents were provided with the questionnaires which they used to provide relevant information to the researcher. The data collected from the field was analyzed using weighted averages and percentages. The data was presented by use of frequency tables and charts. This study used primary data collected from the respondents of the survey. Data was also analyzed using Statistical Package for the Social Sciences (SPSS) version 21. Regression analysis was used to determine the relationship between strategic change management practices on performance of public institutions. Results: The results revealed that information management positively affected performance. However the employees needed more training in such, to be efficient. Effective communication process between various departments and staff involved in the change process was found to be an important factor in the successful implementation of the change process. Public institutions have installed computers as a change management strategy. Unique contribution to theory, practice and policy: With the rapid development of information technology, the use of information systems to improve employee performance in organizations is evolving. Organizations are instructed to introduce computer technology in order to develop themselves. The growing utilization of information systems may encourage employees to increasingly use information systems to help them perform tasks and manage work. This will result in rapid development of the electronic government (e-government) concept.